Pendirian Koperasi Makarorrong UPTD SMAN 1 Nosu: Prosedur, Tantangan, dan Manfaat Sebagai Sarana Pendidikaan Kewirausahaan Peserta Didik (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the procedures, challenges, and benefits of establishing the Makarorrong Cooperative at UPTD SMAN 1 Nosu as a means of entrepreneurship education for students. The research used a descriptive qualitative approach with data collection through in-depth interviews, participatory observation, and documentation studies, involving the head of the education unit, deputy head of student affairs, cooperative advisors, and cooperative administrators from teachers and students. The results showed that the establishment of the cooperative was carried out through stages of internal planning meetings, the formation of a founding committee, the drafting of the articles of association, and socialisation to the school community, with the active involvement of all elements of the school as a determining factor for success. However, this process also faced obstacles in the form of limited capital, a lack of managerial training, and minimal external support from the local government. The Makarorrong Cooperative has a positive impact on students, particularly in terms of character building, independence, cooperation, leadership, and a basic understanding of business management gained through hands-on practice. Thus, the cooperative functions not only as a school economic institution but also as a laboratory for entrepreneurship education based on real-world experience. This study confirms that the development of school cooperatives requires a participatory approach and continuous guidance in order to function optimally